Effects of temperature and heat waves on emergency department visits and emergency ambulance dispatches in Pudong New Area, China: a time series analysis - Sun, Xiaoming (BioMed Central, 2014)
BACKGROUND: In July 2013, an extended heat episode with extreme high temperature covered Pudong New Area, the largest district in Shanghai. The current study estimates the impacts of temperature and heat waves on emergency department visits (EDV) and emergency ambulance dispatches (EAD) using time-series approaches in Pudong, from 2011 to 2013. METHODS: An over-dispersed Poisson generalized additive model was used to examine the association between temperature and EDV and EAD. Heat wave effects with different heat wave definitions considering both the intensity and durations were also estimated. RESULTS: Immediate effects of temperature on EDV and EAD were detected, after controlling for trends of time and day of week. The exposure-response relationships showed J-shaped curves with higher threshold temperature of EDV than that of EAD visually. When estimating risk changes on heat days compared with non-heat days using different percentiles of daily mean temperature in definition, EAD showed significant increases while non-significant or even negative associations were found for EDV. Heat wave with intensity above the 90th percentile had 2.62% (95% CI: 1.78%, 3.46%) and 0.95% (95% CI: 0.22%, 1.69%) increases in EDV for a duration of at least 2 days and 3 days respectively. The relative increase of EAD were 4.85% (95% CI: 1.42%, 8.39%) and 3.94% (95% CI: 0.88%, 7.10%). CONCLUSIONS: Varied effects of temperature and heat waves on emergency department visits and emergency ambulance dispatches were investigated. This wider view of the health effect of temperature indicated that interventions for both public health education and health services management should be considered in the study region. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/1476-069X-13-76) contains supplementary material, which is available to authorized users.